Sistem Penjualan Toko Perhiasan Star Silver Berbasis Web - Stanislaus Wahyu Eka Mahendra; Margi Utami; Prihati (Jurnal Cakrawala Informasi, 2024)
Star Silver Jewelry Shop is a business entity that operates in the field of selling silver jewelry. It was discovered that this shop still uses handwritten manual transaction proof. When a business is run manually, of course many problems arise, one of which is difficulty in managing transaction data such as proof of sales, item data, item codes and large amounts of sales results. So this research is here to provide a solution. The type of research used is research and development (R&D). This web-based application was created using the CodeIgniter 3 framework, Tailwind CSS and MYSQL database, with the PHP programming language and a little JavaScript. This website contains a login page as an initial display, where users are required to log in to validate whether the operator behind it is an officer or not, then they will be forwarded to a dashboard page with several customized menus.